Integrasi Sains dan Islam dalam Pendidikan Islam: Model, Tantangan, dan Implementasi di Madrasah dan Pesantren - Harahap, Fatimah Depi Susanty; Arbi, Arbi; Yusrianto, Edi (Kutubkhanah, 2025)
The integration of science and Islam in education is a response to the historical dichotomy between religious knowledge and secular sciences that continues to influence modern Islamic education systems. As core institutions of Islamic education, madrasahs and pesantrens hold strategic potential to promote a holistic and tauhid-based educational paradigm. This study aims to explore the conceptual framework of science-Islam integration, analyze integrative learning models applied in madrasahs and pesantrens, and identify the key challenges and opportunities in its implementation. Employing a qualitative-descriptive approach through literature review and curriculum analysis, this research finds that integration can be realized through tauhid-oriented curricula, contextualizing scientific concepts with Qur’anic verses, and implementing interdisciplinary and holistic learning models. However, significant challenges remain, including a lack of qualified teachers capable of integrating both fields, limited availability of integrative teaching materials, and inadequate laboratory infrastructure. Therefore, this study recommends enhancing teacher competence, developing integrated teaching modules, and fostering collaboration between Islamic schools and Islamic universities. The findings highlight the urgency of constructing an Islamic education model that is not only spiritually grounded but also responsive to scientific and technological advancements.